Analysis of Final Semester Assessment and Fiqih Independent Examination Higher Order Thingking Skill Type - Teti Nurhalizah; Muhammad Ali Ramdhani; Nina Nurmila (Jurnal al-Thullab, 2023)
This study aims to describe the questions based on the level of thinking, type of stimulus and operational verbs used to make questions. This study uses a descriptive approach to document analysis that aims to analyze the questions, provide direction and assess questions according to the cognitive level at the Madrasah Tsanawiyah level. The results showed that of the 135 questions, half of them were about Higher Order Thinking Skills and some were about Lower Order Thinking Skills. The questions in the Higher Order Thinking Skills category were mostly found in 7th grade material regarding Thaharah material, 8th grade material regarding zakat fitrah and 9th grade material regarding the timing of qurban and fasting. The types of stimulus contained in the questions are tables and discourses where the most widely stimulated discourse questions are found in more than 60% of the total questions.Penelitian ini bertujuan untuk mendeskripsikan soal-soal berdasarkan level berpikir level Lower Order Thinking Skills (LOTS) atau Middle Order Thinking Skills (MOTS) atau Higher Order Thinking Skills (HOTS) serta mengelompokkan soal berdasarkan jenis stimulus dan KKO (Kata Kerja Oprasional) yang digunakan untuk membuat pertanyaan. Penelitian ini menggunakan pendekatan deskriptif analisis dokumen. Dokumen yang dianalisis yaitu bertujuan untuk menganalisis lebih mendalam serta memberikan soal-soal rekomendasi HOTS yang bisa digunakan dalam pembelajaran nantinya. Hasil penelitian menunjukkan bahwa dari 135 soal  hanya terdapat setengahnya merupakan soal Higher Order Thinking Skills (HOTS), dan sebagiannya soal Lower Order Thinking Skills (LOTS). Soal kategori Higher Order Thinking Skills (HOTS) paling banyak ditemukan pada materi kelas VII mengenai materi Thoharah, materi kelas 8 mengenai zakat fitrah dan materi kelas 9 mengenai waktu pelaksanaan kurban dan materi puasa, belum ada soal yang memenuhi kriteria Higher Order Thinking Skills (HOTS). Jenis stimulus yang terdapat pada soal adalah table dan wacana dimana penggalan kasus merupakan stimulus yang paling banyak ditemukan lebih dari 60% dari keseluruhan soal.